The Concept of Imk?n al-Ru’yah Sayyid Usman in the Book Iqaz An-Niyam f? Ma Yata?allaq bi Ahillah wa as-Siyam - Hafiz, Zahra Hayati; Ahmad Izzuddin (Universitas Islam Negeri Mataram, 2025)
This research aims to examine the concept of imk?n al-ru’yah according to Sayyid Usman in the book Iqaz an-Niyam fi Ma Yata'allaq bi Ahillah wa as-Siyam and to analyze its relevance to contemporary crescent visibility criteria. The implementation of this research uses a approach qualitative based on a number of literature review, relying on Iqaz an-Niyam fi Ma Yata'allaq bi Ahillah wa as-Siyam as the primary source, along with e-journals, reference books, and relevant literature as secondary sources. The results show that Sayyid Usman's concept of imk?n al-ru’yah is drawn from the views of various scholars, stipulating that in some locations, the new crescent can only be sighted if it reaches a minimum altitude of 7 degrees, while in other places, an altitude of 8 degrees or more is required for visibility. Sayyid Usman's concept of imk?n al-ru’yah remains relevant to contemporary crescent visibility criteria. The relevance between Sayyid Usman's concept of imk?n al-ru’yah and contemporary visibility criteria lies in their common round in establishing crescent visibility standards, despite significant differences in their approaches.